Scientific Perspectives on Autism Over Time - Di Feo, Gian Marco; O’Connell, Michael (Advances in Social Sciences Research Journal, 2022)
Purpose: The study was conducted to examine changes in the beliefs and contents of articles on autism since the mid-twentieth century. Characteristics analyzed were the mentioning of pharmaceutical drugs, country, and institution of the first author, methodologies used, journal, and the year of publication. Methods: All articles (N=566) analyzed were published between January 1st, 1943 and December 31st, 2021. Inter rater reliability was assessed and there was a 94.4 percent agreement amongst raters. All articles were analyzed through both PubMed and PsycInfo. Results: A one way chi square indicated that there was a significant number of articles expressing mixed beliefs on the cause of autism. Scientific perspectives on the cause of autism have changed significantly over time. Particularly, the belief of empiricism (environmental factors) has decreased significantly, while both mixed beliefs and nativism have increased remarkably. Additionally, the mentioning of pharmaceutical drugs is involved with the beliefs on the cause of autism. Conclusion: Articles in the twenty first century are most likely to express both nativist and empiricist viewpoints on the cause of autism. Articles that express mixed beliefs are most likely to mention drugs in their study. The results impact scientific self-understanding on autism and beliefs in high-income countries, and advance scientific understanding globally.